Audit Quality and Its Determinants: Evidence from Food and Beverage Firms in Indonesia - YUESTI, Anik; PUTRI, Yura Karlinda Wiasa; PUTRA, I Putu Darma; MENES, Carmen C; MADRIGAL, Dennis V. (PT. Keberlanjutan Strategis Indonesia, 2025)
Purpose:This study was conducted to address the importance of audit quality in maintaining the credibility of financial statements of manufacturing companies, particularly in the food and beverage subsector, which contributes significantly to the national economy. The study also aims to respond to the inconsistency of previous research findings regarding the factors that influence audit quality.Methodology:This research utilized a quantitative approach with logistic regression analysis, focusing on food and beverage manufacturing companies listed on the Indonesia Stock Exchange from 2021 to 2023. Using purposive sampling, 49 firms were selected with a total of 147 observations, and the data was sourced from annual financial statements on the IDX website.Findings:The results of the study indicate that public accounting firm size and firm size have a positive influence on audit quality. Companies audited by large accounting firms and those with larger scales tend to produce more reliable financial statements. In contrast, audit fees, audit tenure, and firm age do not show a significant effect on audit quality. These findings affirm that not all external factors related to the company or the auditor play an equal role in determining the quality of audit outcomes.Implication:This study implies that both company management and policymakers should consider the credibility and size of public accounting firms when appointing external auditors, as well as use these findings to develop more effective audit governance policies that enhance stakeholders' trust in financial statements.